Analgesic effects of ultrasound-guided four-quadrant transabdominal plane block in patients with cytoreductive surgery with hyperthermic intraperitoneal chemotherapy: a prospective, randomized, controlled study - 송재격; Choi Nayoung; Kang Minji; 지성미; 김동욱; 권민아 (Anesthesia and pain medicine (Korean society of anesthesiologists), 2022)
Background: Postoperative pain occurring after cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is difficult to control because of extensive surgical injuries and long incisions. We assessed whether the addition of a four-quadrant transabdominal plane (4Q-TAP) block could help in analgesic control.Methods: Seventy-two patients scheduled to undergo elective CRS with HIPEC and intravenous patient-controlled analgesia (IV PCA) were enrolled. The patients received 4Q-TAP blocks in a 10 ml mixture of 2% lidocaine and 0.75% ropivacaine per site (4Q-TAP group, n = 36) or normal saline (control group, n = 33). Oxycodone in the post-anesthesia care unit (PACU) and pethidine or tramadol in the ward were used as rescue analgesics. The primary outcome was less than 3 times of rescue analgesic administration (%) in the ward for 5 postoperative days. Secondary endpoints included oxycodone requirement in PACU, fentanyl doses of IV PCA, morphine milligram equivalent (MME) of total opioid use, hospital stay, and postoperative complications. Results: During 5 postoperative days, there was no difference in pain scores and total rescue analgesic administration between two groups. However, the use of oxycodone in PACU (P = 0.011), fentanyl requirement in IV PCA (P = 0.029), and MME/kg of total opioid use (median, 2.35 vs. 3.21 mg/kg, P = 0.009) were significantly smaller in the 4Q-TAP group. Hospital stay and incidence of postoperative morbidity were similar in both groups. Conclusions: The 4Q-TAP block enhanced multimodal analgesia and decreased opioid requirements in patients with CRS with HIPEC, but did not change postoperative recovery outcomes. KCI Citation Count: 0